1979
DOI: 10.1007/bf01556108
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of gastrin and secretin

Abstract: In order to determine whether the uptake of gastrin and secretin is limited to specific organ systems (especially the kidney) or whether loss is a nonspecific occurrence across all capillary beds, we have measured the uptake of endogenous and exogenous gastrin and secretin in 32 anesthetized dogs. In 6 dogs, antral irrigation with 0.5% acetylcholine solution produced a brisk increase in gastrin concentrations measured in blood from the aorta. Concentrations in blood from the renal, jugular, and femoral veins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Strunz et al [20] and Thompson et al [23] have shown that removal of gastrin upon transit through the vascular beds of the kid ney, intestine, head and hind leg, was about the same in dogs, which suggests that the mechanism of removal is not specific to any one organ. Recently, Peterson et al [16] have shown that gastrin degradation in man is not confined to certain specific organs, but takes place in many organs, or perhaps in the total volume of distribution for gastrin.…”
Section: Discussionmentioning
confidence: 93%
“…Strunz et al [20] and Thompson et al [23] have shown that removal of gastrin upon transit through the vascular beds of the kid ney, intestine, head and hind leg, was about the same in dogs, which suggests that the mechanism of removal is not specific to any one organ. Recently, Peterson et al [16] have shown that gastrin degradation in man is not confined to certain specific organs, but takes place in many organs, or perhaps in the total volume of distribution for gastrin.…”
Section: Discussionmentioning
confidence: 93%
“…Elimination of gastrin has been recorded in kidneys, intestines, hindlimb. and head [8][9][10]. The lack of a significant extraction of amidated and glycineextended gastrin in the gut does not preclude elimination…”
Section: Discussionmentioning
confidence: 99%
“…Gastrin is produced in antral G-cells by cleavage of progastrin into bioactive peptides of different chain length [1], The peptides undergo various covalent mod ifications including conversion of glycine-extended pro cessing intermediates to carboxyamidated bioactive gas trins [2][3][4], The glycine-extended precursors are released to circulation together with the active carboxyamidated gastrins [5][6][7], Studies in dog and sheep have shown that gastrin is cleared from plasma in several vascular beds [8][9][10], After release from G-cells, gastrin peptides pass the liver to enter the systemic circulation. The role of the liver in gastrin metabolism is, therefore, of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Secretin has a relatively short half-life in plasma in humans (2.5-4.0 min) ( 34 37 ). Animal studies have revealed that secretin removal from the circulation occurs mainly through the kidneys ( 38 ) but also the capillary beds of various other tissues ( 39 , 40 ). Despite the kidneys being an important organ for secretin removal, only small amounts of secretin appear in the urine ( 41 ) because, after glomerular filtration, secretin is reabsorbed in the distal part of the nephron ( 42 , 43 ).…”
Section: Pharmacokineticsmentioning
confidence: 99%